A Patient With Erdheim-Chester Disease Presenting With Intestinal Obstruction as the Initial Symptom: A Case Report - Zhou, Xiuzhi; Zhai, Duchang; Yang, Junlin; Shi, Dai; Lu, Kuan; Cai, Wu; Fan, Guohua; Ju, Shenghong (Frontiers in Oncology, 2022)
Erdheim-Chester disease (ECD) is a rare and systemic non-Langerhans cell histiocytosis. Recently, ECD was classified as an inflammatory medullary tumor that affects a diverse group of organ systems. The purpose of this report is to present the radiological features of this disease in a 51-year-old man with intestinal obstruction as the initial presentation. In this case, X-ray computed tomography (CT) and emission computed tomography (ECT) clearly showed lesions in various systems, especially in the skeletal images. The survival benefit of treatment with interferon α (IFN-α) and BRAF inhibitors is well established, while other treatments focus on symptom relief.